2022
DOI: 10.1186/s12917-022-03475-2
|View full text |Cite
|
Sign up to set email alerts
|

Donor age effects on in vitro chondrogenic and osteogenic differentiation performance of equine bone marrow- and adipose tissue-derived mesenchymal stromal cells

Abstract: Background Bone marrow (BM)- and adipose tissue (AT)-derived mesenchymal stromal cells (MSCs) have shown potential as cell-based therapies for cartilage and bone injuries and are used increasingly in human and veterinary practice to facilitate the treatment of orthopedic conditions. However, human and rodent studies have documented a sharp decline in chondrogenic and osteogenic differentiation potential with increasing donor age, which may be problematic for the important demographic of older o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
(89 reference statements)
0
12
0
1
Order By: Relevance
“…Aging is positively correlated with the number of senescent articular chondrocytes and osteoarthritis progression [33]. It is therefore important to consider cellular senescence as a contributing factor in the pathophysiology of osteoarthritis and in therapeutic stem cell potential [13, 34]. SA‐BGAL activity is considered a gold‐standard biomarker of cellular senescence associated with increased size and activity of the lysosomal compartment, which releases lipofuscin [26, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is positively correlated with the number of senescent articular chondrocytes and osteoarthritis progression [33]. It is therefore important to consider cellular senescence as a contributing factor in the pathophysiology of osteoarthritis and in therapeutic stem cell potential [13, 34]. SA‐BGAL activity is considered a gold‐standard biomarker of cellular senescence associated with increased size and activity of the lysosomal compartment, which releases lipofuscin [26, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation and biobanking of stem cells are important for research purposes and for treatment of aged patients, as aging has demonstrated negative effects on the potential of AT-derived stem cells when treating osteoarthritis [13][14][15][16]. Cryopreservation potentially opens the possibility to store functional stem cells from an early age for use later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of equine stem cells derived from bone marrow, adipose, and synovial fluid have demonstrated progressive reductions in cell proliferation and differentiation potential, as well as increased prevalence of age-related binucleate or tetraploid cells. Additionally, stem cells derived from geriatric horses are more likely to show morphological features correlated with aging such as endoplasmic reticulum stress, autophagy, and mitophagy [55][56][57][58].…”
Section: Cell Populationsmentioning
confidence: 99%
“…There are at least two interesting points associated with this perspective; (1) there could be specific loss of PNRC numbers or functioning with aging [ 106 ] and life-span transitions, which would put the health and functioning of the other cells in a brain centre at risk; (2) it would be better to attempt to restore function earlier rather than later in a disease process when the number of residual cells is still prominent. Regarding Point 1, it is known that the numbers and function of PMRC/MSC decline with age [ 107 , 108 , 109 ] and the brain-associated NSC as defined by Reynolds et al [ 1 , 2 ] act as a reservoir of pluripotent cells for replenishment of small numbers of NSC that are required in a subclinical manner for, perhaps, maintenance of tissue integrity. Regarding Point 2, the medical model of relying on drugs during the early stages of disease and only entertaining serious, potentially more risky interventions until late in the disease process actually works against the concept of restoration of function when there are sufficient residual cell numbers in the affected tissues to make the restoration of function with NSC more achievable.…”
Section: The Way Forwardmentioning
confidence: 99%